How TOMS' "one day without shoes" campaign brings stakeholders together and co-creates value for the brand using Instagram as a platform. Issue 3 (11th July 2016) - Roncha, Ana; Radclyffe-Thomas, Natascha
Abstract : Purpose: – The purpose of this paper is to demonstrate the power of social media networks, namely Instagram, in building brand communities and co-creating value for brands. By analysing the 2015 campaign #withoutshoes by TOMS, the authors intend to demonstrate how the value creation process can be extended to involve all stakeholders and raise the effectiveness of a brand's communication campaign. Design/methodology/approach: – A qualitative approach was taken to enable an understanding of online consumer behaviour. A series of qualitative semi-structured interviews were conducted with retail and marketing professionals from the TOMS brand to explore brand strategy. The TOMS Instagram account was analysed for a specific marketing communications event and summative content analysis was applied to the brand's Instagram profile in order to allow for an in-depth exploration of the co-creation process. Triangulation was used for the multiple sources of evidence in order to build the study and to establish the convergence of data results, to diminish bias and to increase accuracy of the research data (Saunders et al., 2009). Findings: – Through a detailed overview of the campaign developed by TOMS, this paper explores how TOMS fosters the formation of consumer-brand-relationships as well as maps out the advantages of value co-creation. The research findings support the literature on co-creation, which argues that the way to achieve innovation and value creation in the changing and challenging marketing landscape is through co-creation. This study adds to the findings that co-creation strategies are a privileged manner of nurturing customer relationships and of lowering costs for marketing and research and development (Sawhney et al., 2005; Prandelli et al., 2006). Originality/value: – There are a relatively limited number of studies focusing on the Instagram platform, and of those carried out thus far most concentrate on how the platform interprets cultural issues, rather than how it can be used effectively as a marketing strategy and how it can leverage user's preferences. Also, not a lot of studies have focused on the relationship between value co-creation and its relevance and impact on brands through engagement processes and the role of experience in brand building. Brand value co-creation through human experiences can provide considerable implications for brand management (Prahalad and Ramaswamy, 2004a) as well as be a key component in the building process of customer experiences. This study suggests new approaches to getting useful insights about how brands can use social media to further engage with their target audience though an integrative framework of brand value co-creation with theoretical underpinning.